Online Result Processing System for Secondary Schools - Henry Kelechi, Ezema; Ogbuokiri, Blessing (International Journal of Computer Sciences and Engineering, 2022)
Result Processing is a core academic activity carried out in the secondary school setting. The development of an online result procedure for secondary schools was motivated by the need for accurate and timely result calculation for secondary schools student. With the digitized system, the schools are ensured of a centralized online storage system for management and dissemination of student result. After careful observation and analysis the existing manual process, the manual method was converted into an automated system. The manual method of result computation was modeled with an object-oriented methodology and this resulting system was implemented with a scripting language (PHP), also MySQL was employed as the database management systems for the project. This provided a robust admin interface for the various key players in this sector to actualize their duties in a convenient and responsive system. The final output of this research work produced a system that automates result processing in secondary schools, which can be used in any secondary school in Nigeria.